ÚSh DIAGONALLÍ MATRICAǴA IYE SATSDI AYDAW USÍLÍNDA SANLÍ ShEShIW HÁM KOMPYUTERDE MODELLESTIRIW - Qazimbetova, M.M.; Nurullaev, J.A. (SCIENCE and SOCIETY, 2025)
The article discusses an efficient numerical algorithm for solving a system of linear algebraic equations (SLAE) with a tridiagonal matrix — the Thomas algorithm (also known as the tridiagonal matrix algorithm, TDMA). The step-by-step description of the algorithm, its advantages, limitations, and applications are provided. The implementation of the developed software product based on this algorithm is also presented. The article is enriched with examples of practical applications.
Keywords: tridiagonal matrix; Thomas algorithm (TDMA); Gauss method; Jacobi matrix; difference matrix; main diagonal; Thomas coefficients; symmetric matrix; recurrence relations; diagonal dominance condition; boundary conditions